Pancasila as a Paradigm in Indonesia's People's Economic Develompment - Syelia Febriani; Firga Nevi; Masduki Asbari (AGUSPATI RESEARCH INSTITUTA, 2022)
The purpose of this paper is to find out the people's economy as a paradigm in Indonesia's economic development. From the discussion, it can be concluded that the essence of Pancasila's position as a development paradigm means that it must be based on the values contained in the Pancasila precepts in all aspects of national development. From these contributions it can be concluded that Pancasila as a paradigm has a close relationship with the life of society, nation and state. Because Pancasila plays a very important role in various fields such as law, economy, social culture and development. Pancasila as a paradigm of national development in the economic field requires that every state economic development be based on the morality of the principles of Pancasila, namely the development of a people's economy and rests on the common good. One of them is the introduction of a people's economy as the basis of Indonesia's economic system.